Means of multichannel systems of visualization - Дудковський, С.М.; Синєглазов, В.М. (Proceedings of National Aviation University, 2005)
Multichannel system soft hardware of visualization referenced to aircraft industry is considered in this issue. System components, their general characteristics and CAD data visualization requirements for high tech production designing are included. Application of multichannel system of visualization allows CAD data large screen visualizing in stereo image mode, which provides real-time, three-dimensional high-quality project representation to users.